Histoire et épistémologie des savoirs locaux et autochtones - Marie Roué (Revue d'ethnoécologie)
In this paper, we will attempt an anthropological history of the concept of “local knowledge”, from the first research dedicated to the botanical or zoological knowledge of “traditional” peoples carried out in the 50’s, to the outburst of interest on behalf of actors as disparate as the World Bank, conservation and development NGOs, governments, biodiversity managers, not to mention the main stakeholders, i.e. indigenous peoples and local specialised groups.Through the history of different networks that contributed to developing the concept of local knowledge, traditional or indigenous ecological knowledge, we will highlight precursors and replace them in their heuristic context. We will also consider more recent trends, since the inclusion of traditional knowledge in several international conventions, particularly the Convention on Biodiversity. We will finally examine the epistemological impact of the combination of local knowledge and scientific and lay knowledge.